The Influence of Shopee Digital Marketing, Influencer Marketing, Online Customer Reviews on Purchasing Decisions at Diva Solo Stores during the Pandemic - Lucy Puspitasari; Basuki Nugroho (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the effect of Digital Marketing Shopee, Influencer Marketing, Customer Online Reviews on Purchase Decisions using linear regression analysis. The population in this study were Diva Solo Shop`s consumers who had purchased Diva Solo Shop products. This study determines several sample criteria that will be used in 75 sampling respondents qustioanarries, namely: respondents who have bought or used products at the Diva Solo Store, respondents are male or female, and respondents ages between 21 years to 35 years. The results of data analysis show that the Digital Marketing Shopee variable has a partial influence on purchasing decisions with a t.sig value of 0.000 <0.05. The Influencer Marketing variable has no partial effect on purchasing decisions as shown by the partial test (ttest) with the result of sig 0,454 > 0,05. The Costumer Online Review variable has a partial influence on purchasing decisions as indicated by the partial test (t test) with sig 0.005 <0.05. The variables of Digital Marketing Shopee, Marketing Influencer, Customer Online Review together have an effect on the simultaneous significance value of the F test of (0.000) less than 0.05.